2009
DOI: 10.1097/aln.0b013e3181bf1d79
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Facilitates Glutamatergic Transmission to Neurons of the Ventrolateral Preoptic Nucleus

Abstract: Background There is much evidence that the sedative component of anesthesia is mediated by γ-aminobutyric acid A receptors on hypothalamic neurons responsible for arousal, notably in the tuberomammillary nucleus. These γ-aminobutyric acid A receptors are targeted by GABAergic neurons in the ventrolateral preoptic area (VLPO): when these neurons become active, they inhibit the arousal-producing nuclei and induce sleep. According to recent studies, propofol induces sedation by enhancing VLPO-induced synaptic inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Though the finding of increased c-Fos-immunoreactivity in GABAergic VLPO neurons is congruent with volatile anesthetic-induced activation of sleep-promoting VLPO neurons suggested by previous single label c-Fos expression studies in vivo and by electrophysiological recordings in hypothalamic slices, 18-22 important discrepancies exist. Previous work showed an increase in the absolute number of c-Fos-immunoreactive cells in the VLPO after in vivo isoflurane and halothane exposure, and a significant induction of c-Fos in VLPO following exposure to a subhypnotic dose of isoflurane 22 not reproduced herein.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Though the finding of increased c-Fos-immunoreactivity in GABAergic VLPO neurons is congruent with volatile anesthetic-induced activation of sleep-promoting VLPO neurons suggested by previous single label c-Fos expression studies in vivo and by electrophysiological recordings in hypothalamic slices, 18-22 important discrepancies exist. Previous work showed an increase in the absolute number of c-Fos-immunoreactive cells in the VLPO after in vivo isoflurane and halothane exposure, and a significant induction of c-Fos in VLPO following exposure to a subhypnotic dose of isoflurane 22 not reproduced herein.…”
Section: Discussionsupporting
confidence: 74%
“…17,44,50,53,54 Studies across phyla as distinct as invertebrates and mammals have demonstrated that anesthetic drugs are capable of activating endogenous sleep-promoting neural systems. 18-22,55,56 Hence, we believe that exploring the commonalities and recognizing the key differences in the genesis of these states will be critical to advance our understanding both of anesthetic mechanisms as well as sleep neurobiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GABA and glutamate have been shown to modulate sleep ⁄ wakefulness in the preoptic area (Chou et al, 2003;Gallopin et al, 2000;Stenberg, 2007;Takahashi et al, 2009). Pharmacological manipulation of preoptic area neurons by sedatives such as propofol promotes sleep, whereas activation of glutamatergic neurons in this area promotes wakefulness (Li et al, 2009;Stenberg, 2007;Tung et al, 2001). Therefore, increased Arc density in the preoptic area could contribute to the reduced sleep time seen in EW animals.…”
Section: Discussionmentioning
confidence: 95%
“…Rats with bilateral lesions of the TMN require less isoflurane to induce LORR (Luo & Leung, 2011). In rodent models, general anesthetics such as propofol and isoflurane can increase the inhibitory drive of these VLPO neurons onto the TMN (Luo & Leung, 2011;Nelson et al, 2002), and this could be facilitated by increased excitatory transmission to VLPO by glutamatergic afferents (Li, Guan, Krnjevic, & Ye, 2009). Injection of GABA A agonists onto the TMN inhibits wakefulness (Lin, Sakai, Vanni-Mercier, & Jouvet, 1989).…”
Section: Linking Sleep and General Anesthesia: The Curious Case Of Cmentioning
confidence: 97%